Cardiac Function in Types II and III Spinal Muscular Atrophy: Should We Change Standards of Care? - Bianco, Flaviana; Pane, Marika; D'Amico, Adele; Messina, Sonia; Delogu, Angelica Bibiana; Soraru, Gianni; Pera, Maria Carmela; Mongini, Tiziana; Politano, Luisa; Baranello, Giovanni; Vita, Gianluca; Tiziano, Francesco Danilo; Morandi, Lucia; Bertini, Enrico; Mercuri, Eugenio (Neuropediatrics, 2015)
Objective In the last years, there has been increasing evidence of cardiac involvement in spinal muscular atrophy (SMA). Autonomic dysfunction has been reported in animal models and in several patients with types I and III SMA, these findings raising the question whether heart rate should be routinely investigated in all SMA patients. The aim of our study was to detect possible signs of autonomic dysfunction and, more generally, of cardiac involvement in types II and III SMA.Patients and Methods We retrospectively reviewed 24-hour electrocardiography (ECG) in 157 types II and III SMA patients (age range, 2–74 years). Of them, 82 also had echocardiography.Results None of the patients had signs of bradycardia, atrial fibrillation, or the other previously reported rhythm disturbances regardless of the age at examination or the type of SMA. Echocardiography was also normal. There were no signs of congenital cardiac defects with the exception of one patient with a history of ventricular septal defects.Conclusions Our results suggest that cardiac abnormalities are not common in type II and type III SMA. These findings provide no evidence to support a more accurate cardiac surveillance or changes in the existing standards of care.
Keywords: SMA; cardiac function; standard of care